Heterologous Ad26.COV2.S Prime and mRNA-Based Boost COVID-19 Vaccination Regimens: The SWITCH Trial Protocol - Sablerolles, Roos S. G.; Goorhuis, Abraham; GeurtsvanKessel, Corine H.; de Vries, Rory D.; Huckriede, Anke L. W.; Koopmans, Marion P. G.; Lafeber, Melvin; Postma, Douwe F.; van Baarle, Debbie; Visser, Leo G.; Dalm, Virgil A. S. H.; Kootstra, Neeltje A.; et al. (Frontiers in Immunology, 2021)
The present protocol study was used to summarize the findings of other major COVID-19 vaccination trials and provide an outline of our multicenter, single-blind, randomized controlled trial: the SWITCH trial. In the SWITCH, we compare the immunogenicity and reactogenicity of heterologous versus homologous vaccination strategies of COVID-19 vaccines. We recruit Health Care Workers (HCWs) who received ad.26.Cov2.S as their prime (first vaccination). We randomize HCWs in four groups: no boost (second vaccination), ad.26.Cov2.S, mRNA1273, and BNT162b2). The full protocol of the SWITCH trial can be found in the supplementary material.